The Relationship between Organizational Factors and Voluntary Turnover in an Automobile Industry - Wahab, Rabiah Abdul; Lajin, Noor Faizah Mohd (Mediterranean Journal of Social Sciences, 2012)
The purpose of this paper is to examine the relationship between organizational factors with the voluntary turnover. A total of100 workers in the automobile sector were selected as the respondents in answering the questionnaires. The opinion from those peopleabout the factors of voluntary turnover is readily accessible. The result of the study indicates that there are significant relationshipbetween job responsibilities, compensation and benefit, supervision as well as peer relationship with voluntary job turnover. This studyconcludes that, organizational factors may influence the voluntary turnover as the automobile industry is faced with high rate of voluntaryturnover and most of the employees agreed that the factors above contribute to the turnover problems. It can be implied that voluntaryturnover should be reduced in order to maintain the image and profit of the company. Future work suggests that the company must takeaction to solve this issue and in order to retain current employees.